Minitab student version release 12 for Windows - Minitab Inc.; Minitab Inc.; Minitab, Inc. (Pacific Grove : Duxbury Press, 1998)
A student version of the professional statistical software package that imports and exports data, processes it, and describes, analyzes, and displays it in graphic format.
Computer optical disc in pocket.
System requirements for accompanying disc: IBM PC or compatible (486 or higher) ; 16 MB RAM ; 25 MB of free hard ; Windows 95, Windows NT 3.51 or 4.0 ; math coprocessor strongly recommended ; VGA or SVGA monitor ; mouse.
Keywords: Statistics; Statistics -- Software; Mathematical statistics -- Software; Mathematical statistics